EDUCATION STRATEGY FOR GENERATING A TECHNOLOGY-BASED ENTREPRENEURIAL GENERATION - Purnama, Yulian (Technopreneurship and Educational Development Review (TENDER), 2024)
The rapid growth in information and communication technology (ICT) has fundamentally transformed the business landscape, leading to the emergence of new business models and accelerating the pace of change. In this context, it is essential to prepare the next generation with the appropriate skills to face challenges and leverage opportunities offered by the technology revolution. The purpose of this research is to examine education strategies to produce a technology-based entrepreneurial generation. This study is a qualitative literature review aiming to investigate various approaches in academic literature related to the research topic. Data for this research will be retrieved from Google Scholar with a range of years from 2018 to 2023. The study findings indicate that education strategies to produce a technology-based entrepreneurial generation must be comprehensive, holistic, and sustainable. Education should prioritize the development of technical skills, creative thinking, and entrepreneurial attitudes in an inclusive and sustainable learning environment. Additionally, education should integrate project-based learning and real-world experiences, as well as strengthen soft skills essential for success in business.